2015
DOI: 10.1158/1541-7786.mcr-14-0674-t
|View full text |Cite
|
Sign up to set email alerts
|

Transposon Mutagenesis Screen Identifies Potential Lung Cancer Drivers and CUL3 as a Tumor Suppressor

Abstract: Non-small cell lung cancers (NSCLCs) harbor thousands of passenger events that hide genetic drivers. Even highly recurrent events in NSCLC, such as mutations in PTEN, EGFR, KRAS, and ALK, are only detected in, at most, 30% of patients. Thus, many unidentified low-penetrant events are causing a significant portion of lung cancers. To detect low-penetrance drivers of NSCLC a forward genetic screen was performed in mice using the Sleeping Beauty (SB) DNA transposon as a random mutagen to generate lung tumors in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 50 publications
(61 reference statements)
2
31
0
Order By: Relevance
“…In addition, in many cases, only a single transposon insertion was present at a CCG in tumor cells, suggesting that many CCGs are functioning as haploinsufficient TSGs. This is similar to what has been observed in other SB mutagenesis screens performed in solid tumors (18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Sb Mutagenesis Promotes the Development Of Multiple Breast Csupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, in many cases, only a single transposon insertion was present at a CCG in tumor cells, suggesting that many CCGs are functioning as haploinsufficient TSGs. This is similar to what has been observed in other SB mutagenesis screens performed in solid tumors (18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Sb Mutagenesis Promotes the Development Of Multiple Breast Csupporting
confidence: 90%
“…Identification of Trunk Driver Genes. Most CCGs identified by SB mutagenesis are thought to function during late stages of tumor progression (18)(19)(20)(21)(22)(23)(24)(25)(26). To identify the CCGs that function early in mammary tumor development, we selected transposon insertion sites represented by the highest number of sequencing reads (SB insertions in the CCG in ≥3 tumors with ≥9 reads per tumor), arguing that these insertions would be present in the largest number of tumor cells.…”
Section: Sb Mutagenesis Promotes the Development Of Multiple Breast Cmentioning
confidence: 99%
See 1 more Smart Citation
“…S3A and S3B). The p.L127V mutation in CUL3 known as a tumor suppressor in lung cancer (24) was detected in additional subclone of TH3 4R. Meanwhile TH4 and TH6 had additional subclones in specific metastatic tumors ( Supplementary Fig.…”
Section: The Genomic and Transcriptomic Differences Between Multiple mentioning
confidence: 98%
“…The sleeping beauty (SB) transposon system has expanded the use of insertional mutagenesis for the study of many types of cancers (11)(12)(13)(14)(15)(16)(17)(18)(19)(20); and discovered candidate cancer genes (CCG) involved in the EMT and CSC pathways (21)(22)(23). To better understand the genes and pathways involved in the pathogenesis of TNBC, we performed an siRNA validation study of 40 SB-identified breast cancer TS genes identified in an SB mutagenesis screen performed in Pten mutant mice (24).…”
Section: Introductionmentioning
confidence: 99%